2023
DOI: 10.3389/fphys.2023.1201722
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive monitoring of cardiac function through Ballistocardiogram: an algorithm integrating short-time Fourier transform and ensemble empirical mode decomposition

Jingda Feng,
WeiFen Huang,
Jin Jiang
et al.

Abstract: The Ballistocardiogram (BCG) is a vibration signal that is generated by the displacement of the entire body due to the injection of blood during each heartbeat. It has been extensively utilized to monitor heart rate. The morphological features of the BCG signal serve as effective indicators for the identification of atrial fibrillation and heart failure, holding great significance for BCG signal analysis. The IJK-complex identification allows for the estimation of inter-beat intervals (IBI) and enables a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…As shown in Figure 4a,b, the data showed a high correlation coefficient, even for a relatively long 10 min period. It was confirmed that the sheet sensor had high measurement accuracy comparable to ECG [20,35,36]. As our sheet sensor employed a differential amplifier circuit, the elimination of the effects of power-supply noise and the measurement of biological vibrations with a high signal-to-noise ratio are possible.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…As shown in Figure 4a,b, the data showed a high correlation coefficient, even for a relatively long 10 min period. It was confirmed that the sheet sensor had high measurement accuracy comparable to ECG [20,35,36]. As our sheet sensor employed a differential amplifier circuit, the elimination of the effects of power-supply noise and the measurement of biological vibrations with a high signal-to-noise ratio are possible.…”
Section: Resultsmentioning
confidence: 70%
“…Many unobstructive sensing methods observing vital signs, such as heartbeat and respiration, have been evaluated for integration into unobstructive vital sensors that are based on the detection principle of air pressure [6][7][8], water pressure [9], cameras [10,11], microphones [12], load cells [13][14][15], piezoresistive [16], capacitively-coupled electrodes [17], and piezoelectric films [1,[18][19][20][21][22][23][24][25][26][27][28]. Among these, the sheet-type vital sensor using polyvinylidene fluoride (PVDF) as the pressure-sensitive layer is one of the most promising vital 2 of 12 sensors from the perspective of sensitivity and adaptability to various measurement environments [1,18,[21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“… 20 However, the BCG signal can measure a good quality cardiac signal similar to an ECG signal with appropriate signal preprocessing and effectively be analyzed through nonlinear methods. 25 , 26 Nonlinear methods offer a more accurate modeling of physiological signal dynamics, providing greater insights into cardiac state and improving sleep stage classification with non-intrusive devices. 27 …”
Section: Introductionmentioning
confidence: 99%